Timing of peat initiation across the central Congo Basin - Greta C Dargie; Pauline Gulliver; Ian Lawson; Paul J Morris; Bart Crezee; Pierre Bola; Ovide Emba; Nicholas T Girkin; Joseph Kanyama; George E Biddulph; Donna Hawthorne; Déo R V Boukono; et al. (Environmental Research Letters, 2025)
The central Congo Basin contains the world’s most extensive tropical peatland complex, spanning 16.7 million hectares. Until now, radiocarbon dating of basal peats has been limited to 14 samples with poor spatial coverage, and suggested that peat typically initiated during the Holocene. We present 38 new basal dates, improving spatial coverage across the region. Some of the new basal dates are much older than any previous dates, indicating that peat initiated in the central Congo Basin at multiple locations in the Late Pleistocene. Our oldest basal date is 42 300 (41 200–43 800) calibrated years before present, making this one of the world’s oldest extant tropical peatlands, and twice as old as previously believed. The temporal distribution of basal dates suggests that changing climatic wetness has played a role in peat initiation in the region; numerous basal dates correspond with climatically wet phases, whilst few basal dates correspond with dry phases such as the Last Glacial Maximum (LGM). Today we find the central Congo Basin peatlands on wide interfluves between rivers, and on floodplains (mostly of the dendritic left-bank tributaries of the Congo River). We find the oldest basal dates on the floodplains of these left-bank tributaries, indicating a surprisingly high degree of channel stability over many millennia. This contrasts with, for example, peatlands on Amazonian floodplains, which are typically just a few thousand years old. The persistence of peat in the central Congo Basin since before the LGM, likely the most climatically dry period during the last 42 000 yr in this region, suggests that these areas may have played an important biogeographical role as forest refugia during glacial-interglacial cycles.